2019
DOI: 10.24018/ejbmr.2019.4.2.27
|View full text |Cite
|
Sign up to set email alerts
|

The Antecedents of Green Car Purchase Intention among Malaysian Consumers

Abstract: This study aims to empirically examine the relationships among social influence, green labeling, economic incentives, environmental attitude, environmental knowledge, past green purchase behavior and green car purchase intention among the Malaysian consumers. A multi-stage sampling process with proportionate stratified sampling in the first stage and systematic mall intercept method in the second stage was applied in this study. Thereafter, a questionnaire survey was done among consumers aged 18 and above that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…The influence can be triggered or take place when people around them share their views and insights among each other. Social influence is not limited to family circles, but might be from anyone whom they respect, including friends, social influencers (e.g., celebrities), and others [30]. The higher the social pressure that takes place, the more likely it is that people will be influenced in performing the behaviour [26].…”
Section: Subjective Norms and Intention To Purchase A Hybrid Carmentioning
confidence: 99%
“…The influence can be triggered or take place when people around them share their views and insights among each other. Social influence is not limited to family circles, but might be from anyone whom they respect, including friends, social influencers (e.g., celebrities), and others [30]. The higher the social pressure that takes place, the more likely it is that people will be influenced in performing the behaviour [26].…”
Section: Subjective Norms and Intention To Purchase A Hybrid Carmentioning
confidence: 99%
“…Hence, the social-structure is considered as a significant factor influencing consumer purchase-intentions (Lim et al, 2019;Jayaraman et al, 2015;Gopi and Ramayah, 2007).…”
Section: Relationship Between Subjective Norms and Consumer Purchase mentioning
confidence: 99%
“…Hence, based on the literature we have concluded that subjective norms have a significant influence on consumers to buy (or decline) certain products and services and have more extensive influence on buying-intention compared to buyingbehaviour (Ali et al, 2019;Bashir et al, 2019;Qi and Ploeger, 2019;Jaiswal and Kant, 2018;Lai and Cheng, 2016;Yadav and Pathak, 2016;Chen and Chai, 2010;Lee, 2008). Hence, the social-structure is considered as a significant factor influencing consumer purchaseintentions (Lim et al, 2019;Jayaraman et al, 2015;Gopi and Ramayah, 2007). Past literature, however, lacks an explanation into the influence of subjective norms on consumers' purchase-intention regarding HVs in Pakistan.…”
Section: Relationship Between Subjective Norms and Consumer Purchase Intentionmentioning
confidence: 99%
“…Despite consumers’ claims of their concerns for environmental issues and displaying positive attitudes, the claims have not been translated into green purchase behavior (GPB; Wang, 2020 ). The sales of green cars are still far behind traditional engine-powered cars ( Lim et al, 2019 ). Hybrid cars only occupied 2.2% of the total new vehicle market in US market ( Hur et al, 2013 ), and green cars make up only around 2% of vehicles sold annually in Malaysia ( Lim et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The sales of green cars are still far behind traditional engine-powered cars ( Lim et al, 2019 ). Hybrid cars only occupied 2.2% of the total new vehicle market in US market ( Hur et al, 2013 ), and green cars make up only around 2% of vehicles sold annually in Malaysia ( Lim et al, 2019 ). Even in the largest vehicle market, China, green cars only accounted for 4.82% of total vehicles sold in 2019 ( Forward Business Information, 2020 ).…”
Section: Introductionmentioning
confidence: 99%